UNDERSTANDING E-LEARNING SYSTEM ACCEPTANCE: AN EMPIRICAL ANALYSIS OF KEY FACTORS AMONG ELEMENTARY SCHOOL STUDENTS USING TAM MODEL - Adhi Karisma, I Gusti Putu Yoga; Gui, Anderes (Jurnal TAM (Technology Acceptance Model), 2023)
This study explores e-learning system acceptance among elementary school students, focusing on the factors that influence their behavioral intentions. Grounded in established psychological principles, the research investigates the relationships among perceived ease of use (PEOU), perceived usefulness (PU), attitude (ATT), and user intention (UI) within the framework of the Technology Acceptance Model (TAM). The study, involving 330 elementary school student respondents, formulates and validates a set of hypotheses to shed light on the dynamics of e-learning system acceptance. The findings underscore the pivotal role of PU and ATT in shaping students' intentions to use e-learning systems, providing valuable insights into this demographic's specific needs. By highlighting the interconnectedness of key factors, this research contributes to the enhancement of e-learning adoption and effectiveness in elementary education.